International and national studies and the kind of research we need (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
This paper analyzes studies in literatures on advance care planning (ACP), assesses similarities and differences between ACP and shared care planning (SCP). The modest quality of many studies, the fragmentation of evidence available today, dependent on heterogeneous methodology that is not always adequate, and sometimes conflicting results, underscore the lack of evaluation of a holistic approach in the studies published to date on ACP. Additionally, more recent studies highlight the importance of the communicative-relational aspect, and call for contextualizing the new trials on ACP/SCP taking into consideration the care setting and the different needs of patients which are related to the type of disease.
Keywords: Advance care planning; shared care planning; research; clinical trials; methodology